(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Hepatitis C virus (HCV) infection is a serious public health problem throughout the world. Chronic haemodialysis patients are at higher risk for acquiring hepatitis C virus (HCV) infection. Objective:To assess the rate of seroconversion of hepatitis C virus (HCV) infection every month for one year duration, to evaluate the possible associated risk factors and the relationship of hepatitis C virus infection with blood transfusion and duration of hemodialysis. Methods: Fifty seven patients, 37 males (65%) and 20 females (35%), who were on regular haemodialysis in Al-Kadhimiya Teaching Hospital was studied during the period between January 2009 and December 2009. Patients were analyzed monthly with anti –HCV antibodies using a commercial enzyme-linked immuno-sorbant assay BioKit (bioelisa HCV 4.0) and serum Alanin aminotransferase measurements. Results:Twenty three patients (40.3%) were HCV positive of whom, 13 were males (56.5%) and 10 were females (43.5%). History of blood transfusion, number of blood transfusion and duration of haemodialysis, had significant correlation in acquiring HCV infection. Conclusion: Seroconversion of HCV infection was of high rate incidence (40.3%). Duration of HD, history of blood transfusion and number of blood transfusion(s) are factors affect the rate of seroconversion of HCV infection in patients on regular HD. The higher rate of seroconversion of HCV infection needs further research to identify the causes and to establish a well organized prophylactic program by using more sophisticated and accurate investigation. Key words:Hepatitis C virus infection, Hemodialysis, Chronic renal failure